Continuing Education of Library and Information Specialists - Guha, B. (Journal of Information and Knowledge, 1978)
Highlights the need for having programmes for continuing education of library and information specialists. Discusses formal and informal channels of education, and the relative effectiveness of these channels and suggests intensive and specialised forms of continuing education for library and information specialists.